Synthesis of hexagonal close-packed gold nanostructures - Huang, Xiao (2013)
Solid gold is usually most stable as a face-centred cubic (fcc) structure. To date, no one has synthesized a colloidal form of Au that is exclusively hexagonal close-packed (hcp) and stable under ambient conditions. Here we report the first in situ synthesis of dispersible hcp Au square sheets on graphene oxide sheets, which exhibit an edge length of 200–500 nm and a thickness of ~ 2.4 nm (~ 16 Au atomic layers). Interestingly, the Au square sheet transforms from hcp to a fcc structure on exposure to an electron beam during transmission electron microscopy analysis. In addition, as the square sheet grows thicker (from ~ 2.4 to 6 nm), fcc segments begin to appear. A detailed experimental analysis of these structures shows that for structures with ultrasmall dimensions (for example, <~ 6 nm thickness for the square sheets), the previously unobserved pure hcp structure becomes stable and isolable.